Extracorporeal irradiated tumor bone: A reconstruction option in diaphyseal Ewing’s sarcomas - Puri, Ajay (Medknow Publications, 2010)
BACKGROUND: Limb salvage in extremity tumors is now established as an oncologically safe option without compromising long-term survival. En bloc resection followed by extracorporeal radiation and reimplantation is a biological reconstruction option in diaphyseal Ewing’s sarcomas. We analyzed the results of 12 cases of diaphyseal Ewing’s sarcomas treated using this modality. MATERIALS AND METHODS: Between March 2006 and March 2008, 12 patients with Ewing’s sarcoma underwent enbloc resection and reconstruction, with reimplantation of the sterilized tumor bone, after extracorporeal irradiation. There were eight males and four females, with a mean age of 14 years (range 2 to 22 years). The femur was the most common bone involved (n=8) followed by the tibia and the humerus (two cases each). All these patients were non-metastatic at presentation and received chemotherapy as per the existing hospital protocol. The mean length of the bone resected was 20 cm (range 11 to 25 cm). The specimen was irradiated with 50 Gy prior to reimplantation and stabilized with the host bone, using suitable internal fixation. Standard biplanar radiographs were assessed for evidence of union on the follow-up visits. The functional status was assessed using the Musculoskeletal Tumor Society Scoring system at the time of the last follow up. The mean follow up duration was 29 months (range 12 to 57 months). RESULTS: Two patients (17%) had early infection with graft removal, hence are excluded from any analysis of union, however they are included when analysing complications such as infection. Rest 10 cases were analyzed for bony union at the osteotomy sites. Sixteen (84%) of the 19 osteotomy sites united primarily, without any intervention. Implant failure and non-union was seen at three diaphyseal osteotomy sites. The average time for union of all osteotomy sites was 7.2 months (range 3 to 13 months).The average time for union of the metaphyseal osteotomy sites was 5.9 months (range 3 to 12 months) and of diaphyseal osteotomy sites was 8.3 months (range 4 to 13 months). The mean Musculoskeletal Tumor Society Score was 27 (range 19 to 30) with a mean of 27. Nine of the ten patients with lower limb involvement were independent ambulators without additional aids. At the time of the last review, six patients were free of disease and six patients had died from the disease. There were two recurrences around the operative site. Both were associated with disseminated disease and in both the recurrences were in the soft tissue, away from the irradiated graft. CONCLUSION: Extracorporeal irradiation is a useful, convenient technique for limb salvage in diaphyseal Ewing’s sarcomas when there is reasonable residual bone stock. It is oncologically safe and has good functional results. A radiation dose of 50 Gy for sterilizing the bone ensures adequate tumor kill, while minimizing the deleterious effects on the biomechanical and biological properties of the bone. The use of appropriate implants for adequate internal fixation and supplementary bone grafting at the index surgery may help reduce the need for subsequent additional interventions to achieve union. The limitations of this procedure are that it is not applicable in tumor bones that are structurally weak and in bones with pathological fractures.